Spatial–temporal variations in natural disasters during the Ming and Qing dynasties (1368–1911 AD) in the ancient Huizhou region, eastern China - Lu, Shuguang; Wu, Li; Cheng, Xianfu; Xu, Guanglai; Shen, Fei; Li, Chenchen; Hu, Xiaosi; Yang, Baodong; Zhang, Hongmei; Li, Xiaoxue (Frontiers in Earth Science, 2022)
The Little Ice Age (LIA) during the Ming and Qing dynasties was the most abnormal climate event in China in nearly 2,000 years. During this period, the climate was relatively cold and various natural disasters frequently took place. Through locating and compiling relative historical documents, we aimed to quantitatively and systematically analyze the spatial-temporal variations in the natural disasters in the Mt. Huangshan area (Huizhou region) during the Ming and Qing dynasties (1368-1911; all dates are in AD, unless otherwise mentioned). The results show that (1) flood and drought disasters, the major types of disasters in this area during the Ming and Qing dynasties, simultaneously occurred 422 times, accounting for 79.6% of the natural disasters. (2) There was a significant correlation of occurrence frequency of flood and drought disasters and the total natural disasters on a certain time scale. In some years, they even tended to occur simultaneously. In addition to flood and drought disasters, other disasters (hailstorms, windstorms, frosts, and earthquakes) occurred more frequently in the Qing Dynasty than in the Ming Dynasty. The occurrence frequency of natural disasters had a choppy variation pattern over time, with peaks emerging about once a century. The peaks of natural disasters were mainly concentrated at 1471-1490, 1571-1590, 1671-1690, 1751-1770, and 1851-1870. (3) The most frequent natural disasters took place in Wuyuan, followed by Jixi, Shexian, Xiuning, Qimen, and Yixian. More droughts occurred in Jixi and Yixian, while more floods occurred in Wuyuan, Shexian, Qimen, and Xiuning, more frost disasters occurred in Wuyuan, Jixi, and Qimen, and more earthquakes occurred in Wuyuan and Jixi. The occurrence frequency of wind disasters was not high in any of the counties. (4) Flood and drought disasters in the Mt. Huangshan area (Huizhou region) exhibited obvious stage characteristics during the Ming and Qing dynasties, and they changed gradually from droughts to floods, among which the transition from slight drought to slight flooding was the most obvious during 1811-1911. (5) Overall, slight flooding and slight drought situations accounted for the largest percentage of drought and flood disasters in this area during the Ming and Qing dynasties.